2006
DOI: 10.1002/cmdc.200600015
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorine Scan at the Catalytic Center of Thrombin: CF, COH, and COMe Bioisosterism and Fluorine Effects on pKa and log D Values

Abstract: A series of 16 tricyclic thrombin inhibitors was prepared by using the 1,3-dipolar cycloaddition of azomethine ylides derived from 3- or 4-hydroxyproline and 4-bromobenzaldehyde, with N-(4-fluorobenzyl)maleimide as the key step. The terminal pyrrolidine ring of the inhibitors was systematically substituted to explore the potential bioisosteric behavior of C-F, C-OH, and C-OMe residues pointing into the environment of the catalytic center of a serine protease. X-ray crystal structure analyses revealed a distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 52 publications
1
39
0
2
Order By: Relevance
“…[2,[9][10][11][12] In that investigation, we observed that the pK a value of a tertiary non-aromatic amine could be shifted from values of around 10 to below 2 through the cumulative interaction effects of relatively remote functionalities (see Section 2). Simple rules for predictions of amine basicity were subsequently developed based on extensive database mining.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…[2,[9][10][11][12] In that investigation, we observed that the pK a value of a tertiary non-aromatic amine could be shifted from values of around 10 to below 2 through the cumulative interaction effects of relatively remote functionalities (see Section 2). Simple rules for predictions of amine basicity were subsequently developed based on extensive database mining.…”
Section: Introductionmentioning
confidence: 92%
“…[12] Inductive effects are transmitted over two s-pathways, as substituents at positions 8 ((+)-26 to (+)-33) and 7 ((+)-34 to (AE )-41) are both located in b-and g-position to the amine center. With one substituent, the pK a is decreased by amounts of À0.3 to À1.2 relative to the parent compound (AE )-6.…”
Section: Variation Of Substituents Pointing Towards the Oxyanion Holementioning
confidence: 99%
“…The fluorine atoms are significant as they may induce specific interactions in the solid state such as F···H, F···F, F···O=C, F···N and F···S contacts; these properties have been used with success in materials science and crystal engineering, [30][31] in medicinal chemistry in order to design more active drug candidates and have been exemplified by cocrystallized structures of potent therapeutic agents with target enzymes. [32][33][34] Fluorine is also a useful probe in 19 F NMR spectroscopy with potential implications in biology. [35] In addition, the electron-withdrawing effect of fluorine should alter the redox properties of the ligands and metal complexes and could help cocrystallization due to the enhanced volatility of the latter.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of halogens to enhance binding affinity and modulate pharmacokinetic properties is well established in lead optimization [37,38]. In particular, organic fluorine is often used as bioisosteric hydrogen or oxygen replacement [39,40] and has been investigated in detail, including its effects on nonbonded interactions in hydrophobic cavities and polar interactions. In general, fluorinated molecules interact with their targets revealing similar binding poses compared to nonfluorinated analogues, while the chemical properties of the CÀF bond influences binding affinities.…”
Section: Physicochemical Basis Of Protein-ligand Recognitionmentioning
confidence: 99%